Timber for Sports Goods - Limaye, V. D. (Indian Forester, 1952)
Before the partition of India, the Indian sports goods Industry was concentrated in or near Sialkot and the main timber used for the industry was mulberry (Morus alba) supplied from the Chhanga Manga and Lahore Plantations. All these places have now gone into Pakistan territory. Sports goods manufacturers who migrated into India, have been trying to re-establish their old industry but are confronted with the lack of a suitable timber and the matter was represented to the Government. Timber for sports goods must possess a combination of a number of special properties. Ash timber has been used in Europe and America. Indian mulberry was found to be suitable and the demand was met so long from large plantations in West Punjab. Mulberry plantations are also being raised in Uttar Pradesh and the Andamans. The experiments described in this leaflet were undertaken to do a preliminary survey of the properties of the timber produced by these plantations. It is gratifying to note that the plantations are producing suitable timber for meeting the needs of the sports goods Industry. As it is a valuable tree for other purposes also, mulberry deserves to be raised on a larger scale in favourable localities.